Determinants of Energy Intensity Trends in Indian Metallic Industry: A Firm-level Analysis. Issue 3 (June 2023) - Jain, Megha; Kaur, Simrit
Though the demand for industrial energy by manufacturing firms has witnessed substantial growth, not enough evidence exists regarding the energy intensity trends of such firms. Furthermore, empirical evidence on the determinants of energy intensity trends or even the energy intensity levels per se remains limited. Given this gap, the present article analyses the determinants of energy intensity trends (and also the energy intensity levels) of Indian manufacturing firms over the period 2007–2017. This study has been undertaken with special reference to the metallic industry. A sample of 41 firms is analysed by grouping them into 3 categories, namely firms with increasing energy intensity trends (IEITs), decreasing energy intensity trends (DEITs) and relatively constant energy intensity trends (CEITs) over the stated period. Multinomial logistic model (MLM) is employed to examine the determinants of energy intensity trends for the three categories. Our pertinent findings are as follows: firms with higher labour intensity and also older firms have a greater probability of belonging to the category of DEIT firms vis-à-vis the reference category of IEIT firms. Furthermore, size per se does not significantly impact the probability of a firm belonging to any specific category of energy intensity trend; nevertheless, evidence shows that large-sized firms, though old, have a greater probability of belonging to the DEIT category. Rather surprisingly, R&D intensity has been estimated to have a non-significant impact on the probability of belonging to the DEIT group of firms. However, although R&D-intensive firms have a higher profitability, their impacts remain both favourable and significant. Evidence also suggests that an increase in capital intensity and profitability lowers the probability of a firm to belong to the DEIT category. Additionally, a pooled (panel) econometric analysis has also been undertaken wherein the 'level' of energy intensity is considered as the dependent variable and not the 'trend' in energy intensity. Important findings also emerge from this analysis. Finally, we conclude from a broad policy perspective.